Network Laws. - Denning, Peter J. (Communications of the ACM, 2004)
The article focuses on features of computer networks. A network is usually defined as a set of nodes and links. The nodes represent entities such as persons, machines, molecules, documents, or businesses; the links represent relationships between pairs of entities. The Internet is the first vast network to be mapped and carefully measured. Statistical sampling must be used because it is impossible to measure every node. Well-connected nodes tend to attract more connections than poorly connected nodes. Any network meeting these two conditions will evolve into a scale-free state. A node failure means that any path through that node is unusable; it's as though the node and its links were deleted from the network. A random node failure in a scale-free network has negligible effect on connectivity. However, failure of a hub in a scale-free network can significantly damage the network's connectivity. The biggest innovations of our time--Internet, Web, Linux--have been facilitated by open consortia. Many vast networks have no central authority. The responsibility for taking actions, and for coping with their consequences, moves away from hubs and toward the small groups of the network.